SEORANG PENDERITA HEMOFILIA RINGAN DENGAN PERDARAHAN MASIF - Renny A.R, Ni Made; Suega, Ketut (journal of internal medicine; Vol. 7, No. 2 Mei 2006)
Haemophilia A is the most common of the hereditary clotting factor deficiencies, which have defect of absence or low level factor VIII in the plasma. It is a X-linked recessive inheritance disease, with incidence approximately 1 per 10.000 male birth. In the middle of the year 2001,it were reported 314 cases in Indonesia. The clinical features of the bleeding may be shown many various severity, and classified into mild, moderate and severe disease. The clinical severity of the disease correlates with the extent of the factor VIII deficiencies. Diagnostic confirm by specific clinical features, there is a history of the bleeding in the family, and laboratorium examination to measure the factor VIII level in the plasma. We reported a case, male, 46 years old, Balinese, reffered from private hospital with complaining profuse bloody vomiting and blackish stool and has been done blood transfusion for 15 bags, with history of haemophilia confirmed. The history of bleeding before classified patients into a mild disease, but in the present the patient suffered from chronic liver disease and erosive gastritis, that can lead patients has more profuse bleeding. A good respons shown by giving the transfusion of the cryopresipitate and packed red cell.
Keywords: mild haemophilia, massive bleeding.